Agroformations’ role in satisfying the consumer demand and solving the food country security (Economics and region, 2018)
The article focuses on the role of family rural, farms and agricultural holdings in addressing food and social security.
Keywords: food and social security; science-based norms of consumption; agriculture; farms; agricultural holdings